Tumor microenvironment–responsive and modulatory manganese-based nanoenzyme for enhanced tumor immunotherapy - Yang, Qi; Wu, Qiong; Liu, Haiyan; Wu, Jiandong; Ma, Feng; Tian, Xiaofeng (Frontiers in Pharmacology, 2025)
The characteristics of the tumor microenvironment (TME) have a close and internal correlation with the effect of cancer immunotherapy, significantly affecting the progression and metastasis of cancer. The rational design of nanoenzymes that possess the ability to respond to and regulate the TME is driving a new direction in catalytic immunotherapy. In this study, we designed a multifunctional manganese (Mn)-based nanoenzyme that is responsive to acidic pH and overxpressed H2O2 at tumor site and holds capability of modulating hypoxic and immunosuppressive TME for synergistic anti-tumor photothermal/photodynamic/immunotherapy. We found that this artificial nanoenzyme promoted peroxidase-like and catalase-like activities and catalyzed the in-situ decomposition of H2O2, a metabolic waste product in the TME, into ∙OH and O2, resulting in a ROS burst for killing tumors and relieving hypoxic TME to enhance cancer therapy. Besides the photothermal effect and the enhancement of ROS burst-induced immunogenic cell death, combination of Mn2+ released from Mn-based nanoenzyme in acidic TME and programmed death-ligand 1 blockade triggered a significant anti-tumor immune response. A remarkable in vivo synergistic therapeutic effect was achieved with effective inhibition of primary tumor growth and lung metastasis. Therefore, this TME-responsive Mn-based nanoenzyme offers a safe and efficient platform for reversing the immunosuppressive microenvironment and achieving synergistic anti-tumor immunotherapy.